A Comparative Study on Classification of Image Pixels - Ghimire, Santosh (Journal of Institute of Science and Technology, 2015)
In this paper, we perform the comparison between the classification method introduced by Ghimire-Wang and the classification method developed by Liao-Akritas in many images. We show that in all the considered images, the method introduced by Ghimire-Wang works better than the method of Liao-Akritas. Journal of Institute of Science and Technology, 2015, 20(2): 128-135